Risk assessment and risk-driven testing : Third International Workshop, RISK 2015, Berlin, Germany, June 15, 2015 : Revised selected papers /: Third International Workshop, RISK 2015, Berlin, Germany, June 15, 2015 : Revised selected papers. (2015) - Unknown
No abstract available